Gross anatomical features of the insular cortex in schizophrenia and schizotypal personality disorder: Potential relationships with vulnerability, illness stages, and clinical subtypes - Takahashi, Tsutomu; Sasabayashi, Daiki; Takayanagi, Yoichiro; Furuichi, Atsushi; Kobayashi, Haruko; Yuasa, Yusuke; Noguchi, Kyo; Suzuki, Michio (Frontiers in Psychiatry, 2022)
Introduction Patients with schizophrenia have a higher number of insular gyri; however, it currently remains unclear whether the brain characteristics of patients with schizotypal personality disorder (SPD), a mild form of schizophrenia, are similar. It is also unknown whether insular gross anatomical features are associated with the illness stages and clinical subtypes of schizophrenia. Materials and methods This magnetic resonance imaging study examined gross anatomical variations in the insular cortex of 133 patients with schizophrenia, 47 with SPD, and 88 healthy controls. The relationships between the insular gross anatomy and schizophrenia subgroups (71 first-episode and 58 chronic groups, 38 deficit and 37 non-deficit subtype groups) were also investigated. Results The number of insular gyri was higher in the schizophrenia and SPD patients than in the controls, where the patients were characterized by well-developed accessory, middle short, and posterior long insular gyri. The insular gross anatomy did not significantly differ between the first-episode and chronic schizophrenia subgroups; however, the relationship between the developed accessory gyrus and more severe positive symptoms was specific to the first-episode group. The prevalence of a right middle short gyrus was higher in the deficit schizophrenia group than in the non-deficit group. Discussion These findings suggest that schizophrenia and SPD patients may share an altered insular gross morphology as a vulnerability factor associated with early neurodevelopmental anomalies, which may also contribute to positive symptomatology in the early illness stages and clinical subtypes of schizophrenia.